A compact radio frequency identification tag antenna with loaded coupling rings for two‐side anti‐metal design. Issue 12 (29th October 2022) - Niu, Chenchen; Yuan, Jiade; Chen, Zhizhang (David); Xu, Zhimeng
Abstract: A compact ultra‐high frequency radio frequency identification tag antenna loaded with a pair of rectangular coupling rings for two‐side anti‐metal performance is proposed. It evolves from a planar inverted‐F antenna and has the same upper and lower structures. A pair of coupling rings is symmetrically loaded on the inner sides of the upper and lower substrates, and the tag's maximum power transmission coefficient can be achieved when either side of the antenna is placed on a metallic plate. The proposed tag antenna maintains a compact size of 34 mm × 28 mm × 5 mm. The measured results show that it has the lowest sensitivity of −14.8 dBm when the lower side is on a metallic plate and the lowest sensitivity of −14.2 dBm when the upper side is on a metallic plate. The proposed tag antenna is featured in a compact size, low sensitivities, and anti‐metal performance on two sides. It may be used in the areas such as the industrial internet of things.